Vagus Nerve Stimulator implantation in a pregnant woman with drug resistant epilepsy - M. N. Klochkov; S. A. Katyshev; A. V. Vtorov; M. M. Bondareva; T. A. Skoromets; A. G. Naryshkin; A. A. Feygina (Эпилепсия и пароксизмальные состояния)
The aim is to present a case of successful implantation of Vagus Nerve Stimulator (VNS) in a woman with drug resistant epilepsy (DRE) during pregnancy. It is the first case of VNS implantation in the Russian Federation. The implantation, follow-up, and programming were carried out in the Bekhterev National Research Medical Centre of Psychiatry and Neurology, Saint-Petersburg.Material and method. Female patient, 28 y.o., was diagnosed with DRE more than 11 years ago. The course of her epilepsy deteriorated during pregnancy despite of the appropriate antiepileptic treatment. The EEG, MRI, and laboratory tests did not reveal any focal brain lesion that could necessitate surgical resection. After multidisciplinary consultations, no contraindications to VNS procedure were found.Results. The VNS system was implanted in this patient when she was 18-week-pregnant. The procedure resulted in a seizure reduction and allowed the patient to preserve her pregnancy and deliver a healthy child.Conclusions. VNS Therapy® is safe and effective for the treatment of DRE. This successful case of VNS implantation in pregnancy opens new venues for the treatment of DRE in this group of patients. The authors declare the absence of conflict of interest with respect to this publication. All authors contributed equally to this article.